Efeitos climáticos em assembleias macrobentônicas de um estuário tropical da ecorregião marinha leste do Brasil - Gomes, Luiz Eduardo de Oliveira (2017)
Climate change and the intensification of floods and droughts events are expected to significantly alter marine ecosystems. Understand the effects of droughts and floods on estuaries are of utmost importance to understanding the potential climate impacts on estuaries. The Piraque-AçúMirim estuary is a relatively well-preserved ecosystem located in the Eastern Brazilian Marine Ecoregion, and was used as a case study for the understanding of seasonal variations and their influence on benthic assemblages. The monitoring of the Piraquê-Açú-Mirim estuary is one of the most extensive of Brazilian estuaries (n=14 months) and advantageous because the estuary is in an area with evidence of significant decrease in annual average rainfall over the last decade. Here we present a temporal (months) monitoring of precipitation, salinity and temperature of water, and sediments in the estuarine region, whose objective is i) identify temporal changes in sediments and benthic assemblages in the Piraque-Açú-Mirim estuary; and ii) relate the potential influence of the drought event to the sedimentary and macrofaunal properties. Our hypothesis is that macrofaunal assemblages would be different over time and between haline zones responding to changes in salinity and water temperature. Haline zones were defined according to previous environmental data from the estuary and pilot samples with the data logger conductivity/temperature (OnSet) and multiparameter. An El Niño event caused an intense dry season between the years 2015-2016, with drastic reductions in annual precipitation rates during one of the strongest El-Niño recorded since 1950. Salinity and temperature at each haline zone (euhaline and polyhaline) were different between spring and neap tide tides. Temporal pattern of salinity and temperature in the Piraquê-Açú-Mirin estuary changes from dry and wet seasons of 2015 compared to dry season of 2016 resulting in lower daily oscillations in salinity and temperature of the estuary. Mud content throughout the year 2015 was significantly lower than those observed during the Drought season in 2016 (~ 100%). Chlorophyll-a in dry and wet seasons of 2015 were significantly higher than during dry season of 2016. Marine water intrusion in polyhaline zones in the Piraquê-Açú-Mirim estuary likely contributed to the increase of mud content at both euhaline and polyhaline zones. During the monitoring of the Piraquê-Açú-Mirim estuary the benthic assemblages in euhaline and polyhaline zones were dominated by the same few taxa (Magelonidae, Sternaspidae and Capitellidae). However, changes in the composition of the other less abundant and probably less tolerant taxa were observed. Mud content was the main factor that contributed to the temporal changes of the benthic assemblages, and probably shows changes in the estuarine saline profile. Water temperature was related to changes in richness S and Pielou J’, and to changes in the composition of the assemblages of the Piraquê-Açú-Mirim estuary. Our results corroborate that temperature influence changes in benthic assemblages during drought, as well as the reduction of diversity and density of dominant taxa in the Piraquê-Açú-Mirim estuary. Further studies are need to better understand the relationship between climatic dependent variables (e.g. salinity and temperature) and benthic assemblages, as well as the factors controlling their variability. Long-term monitoring projects are still required, especially in underdeveloped and developing countries. In the case of Brazil, these studies are essential to better manage important systems, such as the PiraquêAçú-Mirim estuary and the bays of Todos os Santos and Paranaguá versus the trends caused by the imminent increase in intensity and frequency of droughts in the current century.